Produção familiar orgânica do camarão da malásia (macrobrachium rosenbergii) - Oliveira, Ianna Lucena Rocha de (2016)
Shrimp farming is a production area that has a great representation in the aquaculture sector. It offers wide acceptance and economic interests, but its practice has been associated with major environmental and social impacts, imbuing the distrust and disapproval, and then need to invest in more consistent production models with practices that do not generate negative impacts to ecosystems. Therefore, the present study sought to develop methods and techniques for organic production system of freshwater prawn (Macrobrachium rosenbergii), along with the Fruit Growers Association of the Penha Beach Sea. For this we used a water recirculation system in which water was treated by filter layers and biological processes of two production modules, wherein the first was treated with conventional feed and the second with domestic food produced by the community. The system reached the carrying capacity similar to extensive farming systems with +/- 10 ind/m2 in both treatments. As for growth, the shrimp showed satisfactory development, reaching market size, and the organic shrimp presented the higher mean biomass (25,77g / ind). In assessing the sanitary conditions organic shrimp also had lower contamination values, then better able to sanitization and marketing. Thus, it was attested the feasibility of shrimp farming system and to choose to feed not industrialized, so free of additives, there is the production of healthier bodies and thus better quality for consumption.